Β‐cyclodextrin modified g‐C3N4 nanosheet: a fluorescent drug carrier with ultrahigh drug loading capacity and pH‐responsive release. Issue 2 (9th November 2018) - Liu, Shanshan; Dong, Wei; Zeng, Xiongfeng; Guo, Zhaoliang; Zong, Peixiao; Li, Bingdong; Meng, Xianguang; Zuo, Guifu
Abstract: Background: β‐cyclodextrin modified g‐C3 N4 (β‐CD/g‐C3 N4 ) nanosheets were successfully synthesized and developed as a novel drug carrier of doxorubicin hydrochloride (DOXHCl). The prepared samples were characterized by Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD) and transmission electron microscopy (TEM). The drug‐loading and drug release was measured by a UV–visible spectrophotometer. Moreover, cell viability tests were carried out to evaluate the inhibition ratio of β‐CD/g‐C3 N4 ‐DOXHCl and bulk g‐C3 N4 ‐DOXHCl. Results: The FTIR result confirmed that β‐CD and g‐C3 N4 are linked by hydrogen bonds. The XRD and TEM results showed that β‐CD/g‐C3 N4 has nanosheet structure with size range 150–300 nm. The drug‐loading ratio rises sharply in the first 14 h and reaches a maximum of 93%. Moreover, β‐CD/g‐C3 N4 nanocomplex showed a pH‐responsive DOXHCl release with a release ratio of 80% at pH = 5, which is two times higher than that of bulk g‐C3 N4 . Cell viability tests demonstrated that the β‐CD/g‐C3 N4 ‐DOXHCl exhibit a higher inhibition ratio on MG63 cells than bulk g‐C3 N4 ‐DOXHCl. Conclusion: β‐CD/g‐C3 N4 nanocomplex achieves an ultrahigh drug‐loading capacity and pH‐responsive release and visualization of the cell phagocytic process. The results indicate that the β‐CD/g‐C3 N4 nanocomplex can be developed as a promising luminescence carrier for drug delivery. © 2018 Society of Chemical Industry